-2x+5 x=-3 --original equation-2(-3)+5 --use substitution property6+5 --solve.11 --final answer is 11.
a = 4
r + 11 + 8r = 29
x = 5, y = -1
If: 7+t = 11 Then: t = 11-7 So: t = 4
-2x+5 x=-3 --original equation-2(-3)+5 --use substitution property6+5 --solve.11 --final answer is 11.
a = 4
r + 11 + 8r = 29
4x-y=2, thereforey=4x-2sub y into 3x+2y=6...3x+8x-4=611x=10x=10/11
9y subtract 11 equals 7
x = 5, y = -1
x=4 x=0
r + 11 = 19 r + 11 - 11 = 19 - 11 r = 8
If: 7+t = 11 Then: t = 11-7 So: t = 4
You subtract 11 from both sides and r equals negative 7. See... r+11=3 -11 -11 r=7
q = 78
6a + 5a = -11 Combining like terms: 11a = -11 Dividing by 11: a = -1